Post-Renaissance Art as a Dissipative System - Vlasov, Victor G. (Actual Problems of Theory and History of Art, 2016)
At the age of “after postmodernism” the studies of post-Renaissance art go beyond the traditional history and are governed by the rules of the systematic interdisciplinary approach. In the second half of the 20th century, the development of structural linguistics promoted the emergence of post-structuralism where the classical “picture of the world” has been interpreted as a transition from chaos to order. The purpose of this method is to study phenomena and processes as dynamic self-organizing systems. It is assumed that the laws of self-organization are universal having in mind the transition from lower to higher forms and, therefore, applicable to the study of classical art and culture. Thus, we can call the art systems “dissipative” (from lat. dissipatio — “dispersion”). The features of dissipative structures were first described by I. R. Prigogine in 1947. According to him, a part of the energy of regular processes can go over to the energy of irregular processes. Therefore, in the so-called non-equilibrium systems unexpected qualitative leaps can lead to more complex internal structure. This is true for the artist’s behaviour and for the structure of the creative process. Works of art represent a unique fusion of universal laws, individual characteristics and unpredictable factors. This understanding of art is essential for the Theory of progressive cyclic development of art by F. I. Schmidt. The article shows the prospects for the further development of this theory.
Keywords: arrhythmology; dissipative system; cluster analysis; protorenaissance; post-structuralism; rhizome; synergetics